Solid electrolyte membrane and preparation method and application thereof

By using a solid electrolyte membrane with high ionic conductivity and stability in lithium-ion batteries, the safety hazards and low energy density of traditional lithium-ion batteries are solved, and the stability and life of the battery are significantly improved.

CN119253042APending Publication Date: 2025-01-03ENVISION AESC JAPAN LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411545102.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries use flammable organic liquid electrolytes with low energy density. The sulfide solid electrolytes are easy to decompose in the air and have poor compatibility with lithium metal negative electrodes, resulting in a short circuit in the battery.

Method used

A solid electrolyte membrane, including binder and sulfide solid electrolyte, is prepared by ball milling and calcining treatment with the binder to prepare a film with high ionic conductivity and stability for use in all-solid lithium-ion batteries. Alloys such as LiCl, Li2O, and Li-Sb/Li-Bi/Li-In are formed to improve the interface properties of the electrolyte/lithium metal negative electrode.

Benefits of technology

It improves the air stability and chemical stability of the electrolyte membrane, inhibits the growth of lithium dendrites, significantly improves the stability and performance of lithium-ion batteries, extends battery life and improves safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253042A_ABST
    Figure CN119253042A_ABST
Patent Text Reader

Abstract

The invention provides a solid electrolyte membrane and a preparation method and application thereof. The solid electrolyte membrane comprises a binder; the molecular formula of the sulfide solid electrolyte is Li P < 1-b > M S < c > O < d > X < e >; wherein, 5lt; a < lt >; 6, 0lt; blt; 1, 1.5 1t; clt; ct; 5, 0lt; dlt; 2.5, 4lt; c + dlt; 5, 1lt; lt, lt; 2; m is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V or Nb; x is selected from one or more of Cl, Br or I; the ionic conductivity of the solid electrolyte membrane is 1 * 10 <-3 > S / cm to 2 * 10 <-2 > S / cm. According to the solid-state electrolyte membrane and the preparation method and application thereof, the stability of the conductivity of the solid-state electrolyte membrane can be improved, the air stability can be enhanced, the electrolyte / active substance interface property can be improved, the service life of an all-solid-state lithium ion battery can be prolonged, and the safety of the all-solid-state lithium ion battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and particularly relates to a solid electrolyte membrane, a preparation method thereof and an application thereof. Background Art

[0002] At present, lithium ion batteries are widely used in fields such as portable electronic devices, electric vehicles and energy storage systems. However, traditional lithium ion batteries use flammable organic liquid electrolytes, which have the disadvantages of potential safety hazards and relatively low energy density, restricting their further development. All-solid-state lithium batteries use solid electrolytes instead of liquid electrolytes, and have higher safety, a wider operating temperature range and higher energy density, which is an important development direction for next-generation battery technologies.

[0003] Sulfide solid electrolytes have become one of the most promising electrolyte materials for all-solid-state lithium batteries due to their high ionic conductivity and good mechanical properties. However, most sulfide electrolytes are easily decomposed in air to generate toxic hydrogen sulfide gas, and the manufacturing conditions are strict, increasing production complexity and cost. In addition, the compatibility of sulfide electrolytes with lithium metal-based anodes is poor, and interfacial reactions are likely to occur, inducing the formation of lithium dendrites and causing battery short circuits. Summary of the Invention

[0004] The present invention provides a solid electrolyte membrane, a preparation method thereof and an application thereof. By means of the solid electrolyte membrane, the preparation method and the application provided by the present invention, the stability of the conductivity of the solid electrolyte membrane can be improved, the air stability can be enhanced, the interface properties between the electrolyte and the active material can be improved, and the service life and safety of all-solid-state lithium ion batteries and lithium batteries can be improved.

[0005] To solve the above technical problems, the present invention provides a solid electrolyte membrane, which at least includes:

[0006] a binder; and

[0007] a sulfide solid electrolyte, the molecular formula of the sulfide solid electrolyte being Li a P 1-b M b S c O d X e ; wherein, 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V or Nb; X is selected from one or more of Cl, Br or I;

[0008] The ionic conductivity of the solid electrolyte membrane is 1×10 -3 S / cm to 2×10 -2 S / cm.

[0009] In one embodiment of the present invention, M is one or more of Sb, In or Bi.

[0010] In one embodiment of the present invention, X is Cl; the value range of b is 0 <b≤0.1。

[0011] In one embodiment of the present invention, the thickness of the solid electrolyte membrane is 1 μm to 200 μm.

[0012] In one embodiment of the present invention, the mass ratio of the binder to the sulfide solid electrolyte is 0.1:99.9 to 10:90.

[0013] The present invention also provides a method for preparing the solid electrolyte membrane, comprising the steps of:

[0014] According to the chemical formula of the sulfide solid electrolyte, the raw materials are mixed evenly according to the stoichiometric amount, and then placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder;

[0015] calcining the sulfide solid electrolyte precursor powder at a preset temperature to obtain the sulfide solid electrolyte; and

[0016] The sulfide solid electrolyte is mixed with a binder, and the solid electrolyte membrane is obtained by dry preparation or wet preparation.

[0017] In one embodiment of the present invention, the raw materials include a Li source, a P source, an M source, an S source and an X source, the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S; the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5; the M source is selected from one or more of oxides of M or sulfides of M; the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, As2S5, As2S3, Sb2S5, Sb2S3, Bi2S5, Bi2S3, Al2S3, Ga2S3, In2S3 or Sc2S3; the X source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2; the O element in the chemical formula comes from the oxide of M.

[0018] In one embodiment of the present invention, when the solid electrolyte membrane is prepared by a dry method, the binder is selected from a first binder, and the first binder is selected from one or more of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

[0019] In one embodiment of the present invention, when the solid electrolyte membrane is prepared by a wet method, the binder is selected from a second binder, and the second binder is selected from one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid, polyurethane, polyvinyl alcohol, sodium alginate, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-cyclodextrin polymer, polypropylene emulsion, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

[0020] The present invention also provides an all-solid-state lithium-ion battery, comprising at least:

[0021] A positive electrode sheet, wherein the positive electrode sheet comprises a halide solid electrolyte, wherein the halide solid electrolyte comprises Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 ;

[0022] A negative electrode; and

[0023] A solid electrolyte membrane is provided between the adjacent positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane is selected from the solid electrolyte membranes described above.

[0024] The present invention also provides an electronic device, comprising the all-solid-state lithium-ion battery described above.

[0025] In summary, the present invention proposes a solid electrolyte membrane and its preparation method and application, which increases the intrinsic resistance of the solid electrolyte membrane to atmospheric degradation, effectively reduces the generation of H2S, increases the possibility of the battery in actual production, and thus enhances the air stability and chemical stability of the sulfide solid electrolyte. It can form LiCl, Li2O and Li-Sb / Li-Bi / Li-In alloys in the electrolyte / lithium metal negative electrode interface layer, can make the electric field uniform, balance the local current density, thereby regulating the nucleation and growth of Li, can effectively inhibit the rapid growth of lithium dendrites at the growth interface, can significantly improve the stability and performance of lithium ion batteries, improve the life and safety of all-solid-state lithium ion batteries. The solid electrolyte membrane has higher stability and specific reactivity, can improve the stability of the conductivity of the solid electrolyte membrane, enhance air stability and improve the electrolyte / active material interface properties, thereby improving the compatibility with active materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0027] Figure 1 Schematic diagram of the process of preparing a solid electrolyte membrane by dry method in one embodiment of the present invention.

[0028] Figure 2 This is a 1C / 1C long cycle performance diagram of the all-solid-state lithium-ion battery in Example 3 at room temperature. DETAILED DESCRIPTION

[0029] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0030] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0031] The technical solution of the present invention is further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The present invention provides a solid electrolyte membrane, which includes a binder and a sulfide solid electrolyte, wherein the molecular formula of the sulfide solid electrolyte is Li a P 1-b M b S c O d X e, where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V, or Nb, etc.; X is selected from one or more of Cl, Br, or I. Among them, introducing M element and O element into the sulfide solid electrolyte rich in halogen elements will form P-O and M-S bonds in the crystal structure, thereby increasing the inherent resistance to atmospheric degradation and effectively reducing the generation of H2S, enhancing the stability of the sulfide solid electrolyte, including being stable to lithium and stable to air, which can facilitate the preparation and operation of the sulfide solid electrolyte. In addition, when using this sulfide solid electrolyte to assemble a all-solid-state lithium-ion battery, alloys such as LiCl, Li2O, and Li-Sb / Li-Bi / Li-In can be formed at the electrolyte / lithium metal negative electrode interface layer. Among them, Li2O has a high intrinsic ionic conductivity, while alloys such as Li-Sb / Li-Bi / Li-In can promote the rapid transfer kinetics of Li + , enabling the electric field to be homogenized, balancing the local current density, and thus regulating the nucleation and growth of Li. In addition, LiCl has a high interfacial energy, which can effectively inhibit the rapid growth of lithium dendrites at the growth interface, can significantly improve the stability and performance of the lithium-ion battery, and improve the lifespan and safety of the all-solid-state lithium-ion battery and the lithium battery.

[0033] In an embodiment of the present invention, M is, for example, selected from one or more of Sb, In, or Bi. Since the ionic radii of Sb, In, or Bi are moderate, the ionic radii of these elements are close to those of the main elements in the sulfide electrolyte, such as sulfur and phosphorus. Therefore, during doping, they can more easily replace the positions of the main elements without causing excessive lattice distortion. And the electronegativity of Sb, In, or Bi is moderate, and they can form stable chemical bonds with the sulfur element in the sulfide, making it difficult to be damaged by external influences. Thus, the sulfide solid electrolyte has high stability and specific reactivity, can improve the stability of the conductivity of the sulfide solid electrolyte, enhance air stability, and improve the electrolyte / active material interface properties, thereby improving the compatibility with the active material.

[0034] In one embodiment of the present invention, X is selected from halogen elements, and depending on the halogen, the degree of anion disorder between the 4a and 4c sites in the crystal structure of the sulfide solid electrolyte is different, ranging from a small amount of anti-site defects when X is I to 60% site disorder when X is Cl, and the lithium conductivity of these compounds mainly depends on the degree of disorder occupied by anion and cation sites. Therefore, X is selected from Cl, for example, to improve the ionic conductivity and electrochemical stability of the sulfide solid electrolyte and improve voltage stability. The value range of b is 0<b≤0.1. In a specific embodiment of the present invention, when M is +5 valence, b is optimally 0.04, and when M is +3 valence, b is optimally 0.02, so as to improve the cycle performance of the lithium ion battery.

[0035] In one embodiment of the present invention, the thickness of the solid electrolyte membrane is, for example, 1 μm to 200 μm, and the ionic conductivity is, for example, 1×10 -3 S / cm~2×10 -2 S / cm, and the ionic conductivity is relatively stable at low temperatures, and the solid electrolyte membrane can be prepared in batches in a dry room with a low dew point, which greatly simplifies the preparation process and reduces the preparation cost. The solid electrolyte membrane provided by the present application can be well matched with the lithium metal negative electrode, and a high-energy-density, high-performance all-solid-state lithium battery can be prepared.

[0036] In one embodiment of the present invention, the mass ratio of the binder to the sulfide solid electrolyte is 0.1:99.9 to 10:90, and the binder is selected from one of the first binder and the second binder. Among them, the first binder is selected from one or more of polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer (ETFE), fluorinated ethylene propylene copolymer (FEP), perfluoroalkoxy resin (PFA), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer, etc. The second binder is selected from PVDF, carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinylpyrrolidone (PVP), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyacrylic acid (PAA), polyurethane, polyvinyl alcohol (PVA), sodium alginate (Alg), ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-cyclodextrin polymer (β-cyclodextrin, β-CDp), polypropylene emulsion (LA132), PTFE, ETFE, FEP, PFA, PCTFE, ECTFE, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer, etc., or one or more thereof. By adding a binder, the processability of the solid electrolyte membrane can be improved, the volume expansion can be alleviated, and the structure of the solid electrolyte membrane can be stabilized.

[0037] The present invention also proposes a method for preparing a solid electrolyte membrane, which is used to prepare the above-mentioned solid electrolyte membrane, and at least includes: according to the chemical formula of the sulfide solid electrolyte, the raw materials are mixed evenly according to the stoichiometric ratio, and then placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder; the sulfide solid electrolyte precursor powder is calcined at a preset temperature to obtain a sulfide solid electrolyte; the sulfide solid electrolyte is mixed with a binder, and a solid electrolyte membrane is obtained by dry preparation or wet preparation.

[0038] In one embodiment of the present invention, according to the chemical formula of the sulfide solid electrolyte Li a P 1-b M b S c O d X e , the Li source, P source, M source, S source and X source are uniformly mixed according to stoichiometric ratio, wherein the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S, the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5, the M source is selected from one or more of oxides of M or sulfides of M, the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, As2S5, As2S3, Sb2S5, Sb2S3, Bi2S5, Bi2S3, Al2S3, Ga2S3, In2S3 or Sc2S3, the X source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2, and the O element in the chemical formula comes from the oxide of M. After the raw materials are evenly mixed, they are placed in a ball mill and ball milled in an inert gas atmosphere, wherein the ball-to-material ratio is, for example, 1:1 to 100:1, the ball milling speed is, for example, 50 rpm to 1500 rpm, and the ball milling time is, for example, 1 h to 48 h, to obtain a sulfide solid electrolyte precursor powder.

[0039] In one embodiment of the present invention, the sulfide solid electrolyte precursor powder is calcined at a preset temperature, wherein the preset temperature is 400° C. to 600° C., and the calcination time is 1 h to 18 h, to obtain a sulfide solid electrolyte.

[0040] See also Figure 1As shown, in one embodiment of the present invention, when the solid electrolyte membrane is prepared by a dry method, for example, a powder extrusion molding method is used, and the binder is selected from the first binder. Specifically, after the sulfide solid electrolyte and the first binder are mixed evenly by low-temperature shearing, they are quickly heated up for high-temperature shearing mixing to obtain a mixed material, and the mixed material is added to a roller press for high-temperature rolling to obtain a solid electrolyte membrane. Among them, the mass ratio of the first binder to the sulfide solid electrolyte is, for example, 0.1:99.9~5:95, the temperature of low-temperature shearing is, for example, -30℃~15℃, the temperature of high-temperature shearing is, for example, 20℃~200℃, and the temperature of high-temperature rolling is, for example, 20℃~200℃. In the dry preparation process, the first binder is wrapped around the sulfide solid electrolyte in a network shape, which can improve the mechanical strength and chemical stability of the solid electrolyte membrane, and can maintain stable contact between the electrolyte and the electrode material during the battery charging and discharging process, thereby improving the performance and life of the battery.

[0041] In one embodiment of the present invention, when the solid electrolyte membrane is prepared by a wet method, for example, a wet coating method and an electrostatic spraying method, the binder is selected from the second binder. Specifically, the sulfide solid electrolyte, the second binder and the solvent are mixed evenly to obtain an electrolyte slurry, and then the electrolyte slurry is coated on the substrate by a wet coating or electrostatic spraying method, and then the substrate coated with the electrolyte slurry is dried and peeled off to obtain a solid electrolyte membrane. Among them, the solvent is, for example, selected from at least one of toluene, chlorobenzene, xylene, dimethyl carbonate, N-methylformamide, n-hexane, glycol dimethyl ether, dibutyl ether, ethanol, 1,2-ethylenediamine, 1,2-ethanedithiol, acetonitrile, tetrahydrofuran, methanol, isopropyl ether, acetone, hexene, ethyl acetate, benzyl acetate, butyl butyrate or diisobutyl ketone. In the electrolyte slurry, the content of the sulfide solid electrolyte is, for example, 30wt% to 90wt%, the content of the second binder is, for example, 0.1wt% to 10wt%, the content of the solvent is, for example, 10wt% to 50wt%, and after drying, the mass ratio of the second binder to the sulfide solid electrolyte is, for example, 0.1:30 to 10:90. The substrate is, for example, selected from polyethylene glycol terephthalate (PET) film, smooth aluminum foil or release paper, etc., for easy demoulding, and the drying temperature is, for example, 30°C to 250°C.

[0042] The present invention also proposes an all-solid-state lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane, wherein the solid electrolyte membrane is arranged between adjacent positive electrode sheets and negative electrode sheets. The positive electrode sheet comprises a positive electrode active material and a halide solid electrolyte, wherein the positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide (NCM), lithium nickel oxide (LNO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium cobalt oxide (LCO) or lithium nickel cobalt aluminum oxide (NCA). The halide solid electrolyte comprises Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 , the halide solid electrolyte does not produce exothermic reaction with the de-lithium positive electrode active material, thereby improving the safety of the lithium-ion battery. The negative electrode plate is, for example, one or more of a metal lithium plate, a metal indium plate, or a lithium-indium alloy plate, and the negative electrode plate includes, for example, a negative electrode active material, and the negative electrode active material is selected from one or more of a graphite material, a silicon material, or a composite material of a graphite material and a silicon material. The solid electrolyte membrane is selected from the above-mentioned solid electrolyte membranes to improve the performance of the all-solid-state lithium-ion battery.

[0043] In one embodiment of the present invention, the positive electrode plate further includes a conductive agent and a binder, wherein the conductive agent is, for example, one or a combination of at least two of conductive carbon black (Super P, SP), carbon nanotubes (Carbon Nano-tube, CNT), vapor grown carbon fiber (Vapor Grown Carbon Fiber, VGCF) or graphene, and the binder is, for example, polytetrafluoroethylene (PTFE) and its derivatives. The mass ratio of the positive electrode active material, the halide solid electrolyte, the conductive agent and the binder is, for example, (65-78): (20-30): (1-3): (1-2). In this embodiment, the mass ratio of the positive electrode active material, the halide solid electrolyte, the conductive agent and the binder is, for example, 69:29:1:1, and the conductive agent is a combination of conductive carbon black (super-P) and vapor grown carbon fiber (VGCF), and the mass ratio of the conductive carbon black and the vapor grown carbon fiber is 1:1, and the binder is, for example, polytetrafluoroethylene. The positive electrode active material, the halide solid electrolyte, the conductive agent and the binder are uniformly mixed to obtain a mixed powder, which is then dry pressed to obtain a positive electrode sheet.

[0044] In one embodiment of the present invention, when the negative electrode plate includes a negative electrode active material, the negative electrode plate also includes a solid electrolyte, a conductive agent, and a binder, etc., wherein the solid electrolyte is, for example, a halide solid electrolyte or a sulfide electrolyte, etc., and this application does not make specific restrictions. The binder is, for example, at least one of polyisoprene, polyethylene, or polypropylene, etc., and the conductive agent is, for example, at least one of carbon nanotubes, carbon fibers, or acetylene black. This application does not limit the ratio of the negative electrode active material, the solid electrolyte, the conductive agent, and the binder, which are selected according to the manufacturing requirements, and the negative electrode plate is, for example, obtained by dry pressing.

[0045] In one embodiment of the present invention, the negative electrode sheet is, for example, a metal lithium sheet, and the positive electrode sheet, the solid electrolyte membrane, and the negative electrode sheet are sequentially stacked, packaged, hot pressed, and cold pressed, and then wrapped with an aluminum plastic film or the like under vacuum or an inert atmosphere to obtain an all-solid-state soft-package lithium-ion battery. The assembly process of the all-solid-state lithium-ion battery is, for example, completed in a glove box with an argon atmosphere.

[0046] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0047] Example 1

[0048] Preparation of sulfide solid electrolyte: 2 mol of Li2S, 1.5 mol of LiCl, 0.48 mol of P2S5 and 0.02 mol of Sb2O5 are milled by high-energy ball milling to obtain precursor powder, where the ball-to-material ratio is 30:1 and the rotation speed is 500 rpm. The precursor powder is sintered at 500°C for 10 hours and Li2S5 is obtained after cooling. 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Sulfide solid electrolyte.

[0049] Preparation of solid electrolyte membrane: electrolyte Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 The mixture is mixed with PTFE at a mass ratio of 99:1 at -20°C, and the temperature is raised to 80°C to make the PTFE fiberized to obtain a mixed material. The mixed material is extruded into a roller press, and the solid electrolyte membrane is rolled to a thickness of 5 μm at 80°C by adjusting the gap of the roller press.

[0050] Preparation of positive electrode: LiNi 0.8 Co0.1 Mn 0.1 O2, conductive agent, Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 The PTFE is prepared by mixing in a mass ratio of 69:1:29:1 and dry-processing to form the positive electrode sheet, and the conductive agent is super-P and VGCF in a mass ratio of 1:1.

[0051] Negative electrode sheet: The negative electrode sheet is made of metal lithium sheet.

[0052] Assembly of all-solid-state batteries: The positive electrode sheets, solid electrolyte membranes and negative electrode sheets prepared above are stacked, packaged, hot-pressed and cold-pressed to form all-solid-state soft-pack batteries.

[0053] Assembly of symmetrical battery: Place the counter electrode Li on both sides of the solid electrolyte membrane and assemble it with the solid electrolyte membrane into a Li / Li symmetrical battery.

[0054] Example 2

[0055] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 10 μm, and other operations were consistent with Example 1.

[0056] Example 3

[0057] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 30 μm. Other operations were consistent with Example 1.

[0058] Example 4

[0059] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 50 μm, and other operations were consistent with Example 1.

[0060] Example 5

[0061] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 100 μm, and other operations were consistent with Example 1.

[0062] Example 6

[0063] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 200 μm, and other operations were consistent with Example 1.

[0064] Example 7

[0065] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.495 mol of P2S5 and 0.005 mol of Sb2O5 is Li5.5 P 0.99 Sb 0.01 S 4.475 O 0.025 Cl 1.5 , other operations remain the same as those in Example 3.

[0066] Example 8

[0067] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.49 mol of P2S5 and 0.01 mol of Sb2O5 is Li 5.5 P 0.98 Sb 0.02 S 4.45 O 0.05 Cl 1.5 , other operations remain the same as those in Example 3.

[0068] Example 9

[0069] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.47 mol of P2S5 and 0.03 mol of Sb2O5 is Li 5.5 P 0.94 Sb 0.06 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.

[0070] Example 10

[0071] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.46 mol of P2S5 and 0.04 mol of Sb2O5 is Li 5.5 P 0.92 Sb 0.08 S 4.3 O 0.20 Cl 1.5 , other operations remain the same as those in Example 3.

[0072] Embodiment 11

[0073] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.5 mol of LiCl, 0.45 mol of P2S5 and 0.05 mol of Sb2O5 is Li 5.5 P 0.9 Sb 0.1 S 4.25 O 0.25 Cl 1.5 , other operations remain the same as those in Example 3.

[0074] Example 12

[0075] The chemical formula of the sulfide solid electrolyte prepared by 1.6 mol Li2S, 1.9 mol LiCl, 0.48 mol P2S5 and 0.02 mol Sb2O5 is Li 5.1 P 0.96 Sb 0.04 S4O 0.10 Cl 1.9 , other operations remain the same as those in Example 3.

[0076] Embodiment 13

[0077] The chemical formula of the sulfide solid electrolyte prepared by 2.4 mol Li2S, 1.1 mol LiCl, 0.48 mol P2S5 and 0.02 mol Sb2O5 is Li 5.9 P 0.96 Sb 0.04 S 4.80 O 0.10 Cl 1.1 , other operations remain the same as those in Example 3.

[0078] Embodiment 14

[0079] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.4 mol of LiCl, 0.1 mol of LiBr, 0.48 mol of P2S5 and 0.02 mol of Sb2O5 is Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.4 Br 0.1 , other operations remain the same as those in Example 3.

[0080] Embodiment 15

[0081] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI, 0.48 mol of P2S5 and 0.02 mol of Sb2O5 is Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.3 Br 0.1 I 0.1 , other operations remain the same as those in Example 3.

[0082] Example 16

[0083] The chemical formula of the sulfide solid electrolyte prepared by 2.01 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.005 mol In2O3 is Li 5.52 P 0.99 In 0.01 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 3.

[0084] Embodiment 17

[0085] The chemical formula of the sulfide solid electrolyte prepared by 2.015 mol Li2S, 1.5 mol LiCl, 0.4925 mol P2S5 and 0.0075 mol In2O3 is Li 5.53 P 0.985 In 0.015 S 4.4775 O 0.0225 Cl 1.5 , other operations remain the same as those in Example 3.

[0086] Embodiment 18

[0087] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.01 mol In2O3 is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.5 , other operations remain the same as those in Example 3.

[0088] Embodiment 19

[0089] The chemical formula of the sulfide solid electrolyte prepared by 2.04 mol Li2S, 1.5 mol LiCl, 0.48 mol P2S5 and 0.02 mol In2O3 is Li 5.58 P 0.96 In 0.04 S 4.44 O 0.06 Cl 1.5 , other operations remain the same as those in Example 3.

[0090] Embodiment 20

[0091] The chemical formula of the sulfide solid electrolyte prepared by 2.06 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.03 mol In2O3 is Li 5.62 P 0.94 In 0.06 S 4.41 O 0.09 Cl 1.5 , other operations remain the same as those in Example 3.

[0092] Embodiment 21

[0093] The chemical formula of the sulfide solid electrolyte prepared by 2.08 mol Li2S, 1.5 mol LiCl, 0.46 mol P2S5 and 0.04 mol In2O3 is Li 5.66 P 0.92 In 0.08 S 4.38 O 0.12 Cl 1.5 , other operations remain the same as those in Example 3.

[0094] Embodiment 22

[0095] The chemical formula of the sulfide solid electrolyte prepared by 2.1 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.05 mol In2O3 is Li 5.7 P 0.9 In 0.1 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.

[0096] Embodiment 23

[0097] The chemical formula of the sulfide solid electrolyte prepared by 1.62 mol Li2S, 1.9 mol LiCl, 0.49 mol P2S5 and 0.01 mol In2O3 is Li 5.14 P 0.98 In 0.02 S 4.07 O 0.03 Cl 1.9 , other operations remain the same as those in Example 3.

[0098] Embodiment 24

[0099] The chemical formula of the sulfide solid electrolyte prepared by 2.42 mol Li2S, 1.1 mol LiCl, 0.49 mol P2S5 and 0.01 mol In2O3 is Li 5.94 P0.98 In 0.02 S 4.87 O 0.03 Cl 1.1 , other operations remain the same as those in Example 3.

[0100] Embodiment 25

[0101] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.4 mol LiCl, 0.1 mol LiBr, 0.49 mol P2S5 and 0.01 mol In2O3 is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.4 Br 0.1 , other operations remain the same as those in Example 3.

[0102] Embodiment 26

[0103] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.01 mol In2O3 is Li 5.54 P 0.98 In 0.02 S 4.47 O 0.03 Cl 1.3 Br 0. 1I 0.1 , other operations remain the same as those in Example 3.

[0104] Embodiment 27

[0105] The chemical formula of the sulfide solid electrolyte prepared by 2.01 mol Li2S, 1.5 mol LiCl, 0.495 mol P2S5 and 0.005 mol Bi2O3 is Li 5.52 P 0.99 Bi 0.01 S 4.485 O 0.015 Cl 1.5 , other operations remain the same as those in Example 3.

[0106] Embodiment 28

[0107] The chemical formula of the sulfide solid electrolyte prepared by 2.015 mol Li2S, 1.5 mol LiCl, 0.4925 mol P2S5 and 0.0075 mol Bi2O3 is Li 5.53 P0.985 Bi 0.015 S 4.4775 O 0.0225 Cl 1.5 , other operations remain the same as those in Example 3.

[0108] Embodiment 29

[0109] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.5 mol LiCl, 0.49 mol P2S5 and 0.01 mol Bi2O3 is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.5 , other operations remain the same as those in Example 3.

[0110] Embodiment 30

[0111] The chemical formula of the sulfide solid electrolyte prepared by 2.04 mol Li2S, 1.5 mol LiCl, 0.48 mol P2S5, and 0.02 mol Bi2O3 is Li 5.58 P 0.96 Bi 0.04 S 4.44 O 0.06 Cl 1.5 , other operations remain the same as those in Example 3.

[0112] Embodiment 31

[0113] The chemical formula of the sulfide solid electrolyte prepared by 2.06 mol Li2S, 1.5 mol LiCl, 0.47 mol P2S5 and 0.03 mol Bi2O3 is Li 5.62 P 0.94 Bi 0.06 S 4.41 O 0.09 Cl 1.5 , other operations remain the same as those in Example 3.

[0114] Embodiment 32

[0115] The chemical formula of the sulfide solid electrolyte prepared by 2.08 mol Li2S, 1.5 mol LiCl, 0.46 mol P2S5 and 0.04 mol Bi2O3 is Li 5.66 P 0.92 Bi 0.08 S 4.38 O 0.12 Cl 1.5 , other operations remain the same as those in Example 3.

[0116] Embodiment 33

[0117] The chemical formula of the sulfide solid electrolyte prepared by 2.1 mol Li2S, 1.5 mol LiCl, 0.45 mol P2S5 and 0.05 mol Bi2O3 is Li 5.7 P 0.9 Bi 0.1 S 4.35 O 0.15 Cl 1.5 , other operations remain the same as those in Example 3.

[0118] Embodiment 34

[0119] The chemical formula of the sulfide solid electrolyte prepared by 1.62 mol Li2S, 1.9 mol LiCl, 0.49 mol P2S5 and 0.01 mol Bi2O3 is Li 5.14 P 0.98 Bi 0.02 S 4.07 O 0.03 Cl 1.9 , other operations remain the same as those in Example 3.

[0120] Embodiment 35

[0121] The chemical formula of the sulfide solid electrolyte prepared by 2.42 mol Li2S, 1.1 mol LiCl, 0.49 mol P2S5 and 0.01 mol Bi2O3 is Li 5.94 P 0.98 Bi 0.02 S 4.87 O 0.03 Cl 1.1 , other operations remain the same as those in Example 3.

[0122] Embodiment 36

[0123] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.4 mol LiCl, 0.1 mol LiBr, 0.49 mol P2S5 and 0.01 mol Bi2O3 is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.4 Br 0.1 , other operations remain the same as those in Example 3.

[0124] Embodiment 37

[0125] The chemical formula of the sulfide solid electrolyte prepared by 2.02 mol Li2S, 1.3 mol LiCl, 0.1 mol LiBr, 0.1 mol LiI, 0.49 mol P2S5 and 0.01 mol Bi2O3 is Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.3 Br 0. 1I 0.1 , other operations remain the same as those in Example 3.

[0126] Embodiment 38

[0127] ETFE was selected as the adhesive, and other operations were consistent with those in Example 3.

[0128] Embodiment 39

[0129] PCTFE was selected as the binder, and other operations were consistent with those in Example 3.

[0130] Embodiment 40

[0131] Preparation of sulfide solid electrolyte: 2 mol of Li2S, 1.5 mol of LiCl, 0.48 mol of P2S5 and 0.02 mol of Sb2O5 are milled by high-energy ball milling to obtain precursor powder, where the ball-to-material ratio is 30:1 and the rotation speed is 500 rpm. The precursor powder is sintered at 500°C for 10 hours and Li2S5 is obtained after cooling. 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 Sulfide solid electrolyte.

[0132] Preparation of solid electrolyte membrane: Li 5.5 P 0.96 Sb 0.04 S 4.40 O 0.10 Cl 1.5 , SBR binder and xylene solvent were evenly mixed in a mass ratio of 49:1:50 to form an electrolyte slurry, and the electrolyte slurry was scraped onto a smooth aluminum foil using a coater, and then vacuum dried and peeled off at 80°C to form a 30μm thick solid electrolyte membrane.

[0133] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent, Li 2.35 Zr 0.65 Fe0.35 Cl5Br 0.5 I 0.5 The PTFE is prepared by mixing in a mass ratio of 69:1:29:1 and dry-processing to form the positive electrode sheet, and the conductive agent is super-P and VGCF in a mass ratio of 1:1.

[0134] Negative electrode sheet: The negative electrode sheet is made of metal lithium sheet.

[0135] Assembly of all-solid-state batteries: The positive electrode sheets, solid electrolyte membranes and negative electrode sheets prepared above are stacked, packaged, hot-pressed and cold-pressed to form all-solid-state soft-pack batteries.

[0136] Assembly of symmetrical battery: Place the counter electrode Li on both sides of the solid electrolyte membrane and assemble it with the solid electrolyte membrane into a Li / Li symmetrical battery.

[0137] Embodiment 41

[0138] PVDF was selected as the binder, and other operations were consistent with Example 40.

[0139] Embodiment 42

[0140] PAA was selected as the binder, and other operations were consistent with Example 40.

[0141] Comparative Example 1

[0142] The chemical formula of the solution prepared by 2 mol of Li2S, 1.5 mol of LiCl, and 0.5 mol of P2S5 is Li 5.5 PS 4.5 Cl 1.5 , other operations remain the same as those in Example 3.

[0143] Comparative Example 2

[0144] The chemical formula of the sulfide solid electrolyte prepared by 2 mol of Li2S, 1.4 mol of LiCl, 0.1 mol of LiBr and 0.5 mol of P2S5 is Li 5.5 PS 4.5 Cl 1.4 Br 0.1 , other operations remain the same as those in Example 3.

[0145] Comparative Example 3

[0146] The chemical formula of the electrolyte prepared by 2 mol of Li2S, 1.3 mol of LiCl, 0.1 mol of LiBr, 0.1 mol of LiI and 0.5 mol of P2S5 is Li 5.5 PS 4.5 Cl 1.3 Br 0.1 I0.1 , other operations remain the same as those in Example 3.

[0147] Comparative Example 4

[0148] By adjusting the roller gap of the roller press, the thickness of the solid electrolyte membrane was prepared to be 1 μm, and other operations were consistent with Example 3.

[0149] In Examples 1-42 and Comparative Examples 1-4 of the present invention, different solid electrolyte membranes are used to test the ionic conductivity of the solid electrolyte membranes, and the solid electrolyte membranes are exposed to a dry room at -40°C for 24 hours, and then the ionic conductivity test is performed again. In this embodiment, the ionic conductivity is obtained, for example, by an AC impedance method, and the test results are shown in Table 1.

[0150] In Examples 1-42 and Comparative Examples 1-4 of the present invention, different sulfide solid electrolytes are used to obtain lithium-ion batteries. At 25°C, the lithium-ion batteries prepared above are subjected to long-cycle charge and discharge, and their discharge capacity is measured, and the energy density is calculated. The operating voltage range of the battery test is 2.5V to 4.3V, the charge and discharge rate is 1C / 1C, and the discharge capacity of the first cycle is recorded as the 1C discharge capacity. When the battery capacity reaches 80% of the first cycle capacity (80% State of Health, 80% SOH), the test is terminated to obtain the number of cycles at room temperature. The symmetrical battery is charged at 1 mA / cm 2 The constant current charge-discharge cycle test was carried out at a current density of , and the test results are shown in Table 2.

[0151] Table 1. Ionic conductivity of sulfide solid electrolytes in Examples 1-42 and Comparative Examples 1-4

[0152]

[0153]

[0154] Table 2. Test results of lithium-ion batteries and symmetrical batteries in Examples 1-42 and Comparative Examples 1-4

[0155]

[0156]

[0157] Please refer to Table 1 and Table 2. By comparing Examples 1-6 and Comparative Example 4, it can be seen that as the thickness of the solid electrolyte membrane increases, the retention rate of the ionic conductivity of the solid electrolyte membrane at low temperatures increases, and the cycle performance of the lithium-ion battery first gradually increases and then gradually decreases. And when the solid electrolyte membrane is too thin, the battery short circuit occurs when the number of cycles is low. Therefore, combined with the retention rate of ionic conductivity and cycle performance, there is an optimal range for the thickness of the solid electrolyte membrane.

[0158] Please refer to Table 1 and Table 2. Comparative Examples 3 and 7-11 show that when the M element in the sulfide solid electrolyte selects Sb, as the doping amount of Sb increases, the cycle performance of the lithium-ion battery gradually increases and then gradually decreases. Comparative Examples 16-22 show that when the M element in the sulfide solid electrolyte selects In, as the doping amount of In increases, the cycle performance of the lithium-ion battery gradually increases and then gradually decreases. In Comparative Examples 27-33, when the M element in the sulfide solid electrolyte selects Bi, as the doping amount of Bi increases, the cycle performance of the lithium-ion battery first gradually increases and then gradually decreases. When the doping amount of Sb, In or Bi elements is too low, the battery short circuit occurs when the number of cycles is small. And as the doping amount of M element increases, the ionic conductivity of the sulfide solid electrolyte decreases, but the ionic conductivity retention rate after exposure to -40°C dry room for 24h increases, enhancing the air stability and chemical stability of the sulfide solid electrolyte, and improving the stability and performance of the battery. This shows that an appropriate amount of M element doping can help form a stable solid electrolyte interface (SEI) and reduce the side reactions between the solid electrolyte and the electrode material. When the doping amount is too low, an effective SEI film may not be formed. Excessive doping will cause excessive lattice distortion and destroy the original crystal structure, which may lead to a decrease in the structural stability of the material and even phase separation or amorphization, thereby reducing the ionic conductivity of the material. Therefore, controlling the doping amount of M in the sulfide solid electrolyte can improve the cycle life and safety of all-solid-state lithium-ion batteries, while maintaining the ionic conductivity at a high level, ensuring the rate performance of lithium-ion batteries, and improving the charge and discharge efficiency and cycle life.

[0159] As shown in Table 1 and Table 2, by comparing Examples 3, 12-13, Examples 18, 23-24, and Examples 29, 34-35, it can be seen that when the doping amount of Sb, In or Bi is the same, increasing or decreasing the Cl element content will cause a serious decrease in ionic conductivity, and will reduce the cycle performance of the lithium ion battery. Therefore, the content of the Cl element is controlled to ensure the ionic conductivity of the sulfide solid electrolyte and the performance of the lithium ion battery.

[0160] Please refer to Table 1 and Table 2. By comparing Examples 3, 14-15, Examples 18, 25-26, and Examples 29, 36- and 37, it can be seen that when the doping amount of Sb, In or Bi is the same, the addition of one or more of Br or I elements will reduce the cycle performance of the battery. This is because the added Br or I may introduce additional lattice defects, which may become obstacles to lithium ion transmission and further reduce the ionic conductivity of the electrolyte. Therefore, X selects Cl element, which can improve the ionic conductivity and electrochemical stability of the sulfide solid electrolyte and improve the voltage stability.

[0161] Please refer to Table 1 and Table 2. Comparison of Examples 3, 14-15, Examples 18, 25-26, Examples 29, 36-37, and Comparative Examples 1-3 shows that when the M element and the O element are not added to the sulfide solid electrolyte, the lithium ion battery has almost no cycle performance and a short circuit occurs quickly, indicating that when the M element and the O element are missing, the chemical stability of the sulfide solid electrolyte material is poor, the mechanical strength is insufficient, and it is difficult to ensure the long-term cycle performance of the lithium ion battery. By introducing the M element and the O element, the cycle performance of the lithium ion battery can be improved.

[0162] Please refer to Table 1 and Table 2. Comparative Examples 3 and 38-39 show that in the dry preparation process, when different first binders are selected, the ionic conductivity of the solid electrolyte membrane and the performance of the lithium-ion battery will also be affected. When the first binder is selected from PTFE, the ionic conductivity of the solid electrolyte membrane and the performance of the lithium-ion battery are optimal. Comparative Examples 40-42 show that in the wet preparation process, when different second binders are selected, the ionic conductivity of the solid electrolyte membrane and the performance of the lithium-ion battery will also be affected. When the second binder is selected from PAA, the ionic conductivity of the solid electrolyte membrane and the performance of the lithium-ion battery are optimal. Comparative Examples 3 and 40 show that the solid electrolyte membrane prepared by the dry process is better than the solid electrolyte membrane prepared by the wet process. This is because a large amount of organic solvents are used in the wet process, and the organic solvents react slightly with the electrolyte, thereby reducing the performance of the electrolyte membrane, while the dry process does not introduce solvents.

[0163] See also Figure 2 As shown, in the all-solid-state lithium-ion battery of Example 3, during the cycle at room temperature, the current density used for constant current charging and discharging is 1C, Figure 2It can be seen that at a current density of 1C, the all-solid-state lithium-ion battery in Example 3 still has an energy storage capacity of about 150 mAh / g after 500 cycles, indicating that the sulfide solid electrolyte has excellent reaction kinetics and cycle stability, and the obtained solid electrolyte membrane has a good gain effect on the cycle stability and reaction activity specific capacity of the battery. The all-solid-state lithium-ion battery has excellent specific capacity, rate performance and cycle life.

[0164] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.

[0165] In summary, the present invention proposes a solid electrolyte membrane and a preparation method and application thereof, which increases the intrinsic resistance of the solid electrolyte membrane to atmospheric degradation, effectively reduces the generation of H2S, increases the possibility of the battery in actual production, and thus enhances the air stability and chemical stability of the sulfide solid electrolyte. It can form LiCl, Li2O and Li-Sb / Li-Bi / Li-In alloys in the electrolyte / lithium metal negative electrode interface layer, can make the electric field uniform, balance the local current density, thereby regulating the nucleation and growth of Li, can effectively inhibit the rapid growth of lithium dendrites at the growth interface, can significantly improve the stability and performance of lithium ion batteries, and improve the life and safety of all-solid-state lithium ion batteries. The solid electrolyte membrane has higher stability and specific reactivity, can improve the stability of the conductivity of the solid electrolyte membrane, enhance air stability and improve the electrolyte / active material interface properties, thereby improving compatibility with active materials.

[0166] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0167] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A solid electrolyte membrane, characterized in that: At least: Binder; and Sulfide solid electrolyte, the molecular formula of the sulfide solid electrolyte is Li a P 1-b M b S c O d X e ; wherein, 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, As, V or Nb; X is selected from one or more of Cl, Br or I; The ionic conductivity of the solid electrolyte membrane is 1×10 -3 S / cm~2×10 -2 S / cm.

2. The solid electrolyte membrane according to claim 1, characterized in that M is one or more of Sb, In or Bi.

3. The solid electrolyte membrane according to claim 1, characterized in that X is Cl; the value range of b is 0 <b≤0.1。 4. The solid electrolyte membrane according to claim 1, characterized in that: The solid electrolyte membrane has a thickness of 1 μm to 200 μm.

5. The solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of the binder to the sulfide solid electrolyte is 0.1:99.9 to 10:

90.

6. A method for preparing a solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: Includes steps: According to the chemical formula of the sulfide solid electrolyte, the raw materials are mixed evenly according to the stoichiometric amount, and then placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder; calcining the sulfide solid electrolyte precursor powder at a preset temperature to obtain the sulfide solid electrolyte; as well as The sulfide solid electrolyte is mixed with a binder, and the solid electrolyte membrane is obtained by dry preparation or wet preparation.

7. The method for preparing a solid electrolyte membrane according to claim 6, characterized in that: The raw materials include a Li source, a P source, an M source, an S source and an X source, wherein the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S; the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5; the M source is selected from one or more of M oxides or M sulfides; the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, As2S5, As2S3, Sb2S5, Sb2S3, Bi2S5, Bi2S3, Al2S3, Ga2S3, In2S3 or Sc2S3; the X source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2; and the O element in the chemical formula comes from the oxide of M.

8. The method for preparing a solid electrolyte membrane according to claim 6, characterized in that: When the solid electrolyte membrane is prepared by a dry method, the binder is selected from a first binder, and the first binder is selected from one or more of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

9. The method for preparing a solid electrolyte membrane according to claim 6, characterized in that: When the solid electrolyte membrane is prepared by a wet method, the binder is selected from a second binder, and the second binder is selected from one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl pyrrolidone, polymethyl methacrylate, polyacrylonitrile, polyacrylic acid, polyurethane, polyvinyl alcohol, sodium alginate, ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber, β-cyclodextrin polymer, polypropylene emulsion, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

10. An all-solid-state lithium-ion battery, characterized in that: At least: A positive electrode sheet, wherein the positive electrode sheet comprises a halide solid electrolyte, wherein the halide solid electrolyte comprises Li 2.35 Zr 0.65 Fe 0.35 Cl5Br 0.5 I 0.5 ; A negative electrode; and A solid electrolyte membrane, wherein the solid electrolyte membrane is disposed between the adjacent positive electrode sheet and the negative electrode sheet, and the solid electrolyte membrane is selected from the solid electrolyte membrane according to any one of claims 1 to 5.

11. An electronic device, characterized in that: Including the all-solid-state lithium-ion battery as described in claim 10.

Citation Information

Cited By

  • Preparation method and application of niobium pentoxide doped sulfide solid electrolyte

    CN120637615A

  • Solid-state electrolyte, solid-state electrolyte membrane and preparation method thereof, and solid-state battery

    CN121905944A

  • Solid-state battery cell and preparation method therefor, battery device, and electric device

    WO2026194455A1